Evaluating process and outcomes of interventions for promoting sport participation among South Korean university students - Junhye Kwon; Seiyeong Park; Chiyoung Ahn; Chung Gun Lee (Journal of Men's Health, 2022)
Background: Based on previous research that identified salient beliefs with regard to sport participation among university students, four types of interventions (i.e., social dance class, social dance video, poster, and e-mail) were developed to promote sport participation among the target population. The main purpose of this study is to evaluate the process and outcomes of interventions for promoting sport participation among university students. Methods: The number of views registered on social dance videos and acknowledgements through e-mail were computed to evaluate reach and dose received. Three process evaluators also responded to a 22-item survey and expressed their conceptions on each intervention. Primary and secondary outcomes were analyzed using paired t-tests to assess changes in beliefs and sport participation pre- to post-intervention. Results: Social dance video and poster interventions were relatively more effective in changing target behavior compared to the other two interventions. Following the interventions, students participating in sports less than 150 minutes per week at one-month follow-up were more likely to believe that participating in sports helps them build social relationships, less likely to perceive being tired is bad, and less likely to acknowledge that participating in sports takes too much time. Importantly, the mean duration of sport participation per week increased by 78.49 minutes among students who participated in sport less than 150 minutes per week. Conclusions: The findings of this study suggest that sport participation programs involving video and poster interventions may effectively promote involvement in sporting activities among university students. Future research should implement these interventions in a larger population.